(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
Monoclonal antibodies (mAbs) are unique and specific drug molecules targeting the treatment ofÂ various diseases such as arthritis, immune disorders, infectious diseases, and cancer etc.Â Different methods such as antibody coupled affinity chromatography, hydrophobic interactionÂ chromatography, etc., can be applied to purify mAbs from various sources. This article providesÂ a simple, cost effective, preparative native-polyacrylamide gel electrophoresis (n-PAGE) technique to purify mAbs expressed in H-192 cells (Hybridoma murine cell lines) against anÂ antigen i.e. 17-alpha-hydroxyprogesterone (17-OHP), which further can have diagnosticÂ application to detect Congenital Adrenal Hyperplasia (CAH). Furthermore, different parametersÂ such as concentration and volume of the feedstock (medium containing antibodies), pore size ofÂ gel, height of resolving gel etc. were optimized to obtain the maximum purity and yield of mAbs.